Draft genome sequence data on Bacillus safensis FB03 isolated from the rhizosphere soil of leguminous plant in BangladeshNational Center for Biotechnology Information - Farhana Boby; Dr. Md Nurul Huda Bhuiyan; Dr. Md. Salim Khan; Md. Mashud Parvez (Data in Brief)
With the aim of investigating the biotechnological potential of Bacillus safensis' FB03, isolated from the rhizosphere soil of Bahrind region of Bangladesh, the current work focused on its complete genomic analysis and phenotypic description. The size of the genome of the isolate was 3.6 Mb with 41.59 % GC content. Genome annotation revealed the presence of many genes related to siderophore production, enzyme degradation, UV and stress tolerance. Six biosynthesis gene clusters for bacillibacin, bacilysin, bottromycin, Schizokinen, fengycin, and lychensin were identified through genome mining. Significantly, FB03 was found to contain only two acquired antimicrobial resistance genes and was anticipated to be non-pathogenic to humans. The openness of the Bacillus safensis pan-genome was demonstrated by the pan-genome analysis. According to this research, Bacillus safensis FB03 may be a good fit for a variety of biotechnological applications.